Celiac Disease - Rakhee Sharma (International Journal of Advanced Science and Technology, 2020)
The paper titled “Celiac Disease” is an immune-mediated enteropathy triggered by the ingestion of gluten in genetically susceptible individual. Celiac disease is characterized by small intestinal damage with loss of absorptive villi and hyperplasia of the crypt, typically leading to malabsorption. Reduced levels of iron, folate, vitamin B12,vitamine D, zinc and magnesium are common is untreated celiac disease (CD) patients probably due to loss of brush border proteins and enzymes needed for the absorption of these nutrients.